Seminar Pendidikan Inklusi: Mengenal Lebih Dekat Anak Berkebutuhan Khusus (ABK) - Fitrawati Hasri; Intisari Intisari; Saddaruddin Saddaruddin; Rahmat Permadi (KARYA: Journal of Educational Community Service, 2023)
The community service activity carried out was a PAUD Seminar with the topic Getting to Know Children with Special Needs (ABK) which was held at the Naurah Kindergarten & Play Group. The seminar was attended by four teachers, one principal, one operator, and eight students who are currently participating in the Program MBKM Independent Study at Naurah Kindergarten & Play Group. This is a community service activity. The aim of this service program is to increase the knowledge of teachers and school principals regarding the close knowledge of Children with Special Needs (ABK) and the methods that can be used to handle them. Presentations, lectures and discussions are the implementation methods used in this service. The results of this service activity are measured through assessing Pre-test and Post-test participation in the PAUD seminar material: Getting to Know Children with Special Needs (ABK). Next, the data collected was analyzed using the Wilcoxon Test with the help of SPSS, the results of which showed that the data Asymp (2-tailed) = 0.01 < 0.05, meaning that there was a significant difference between participants' understanding before and after being given the PAUD Seminar. The results of the service showed that there was an increase in awareness of Children with Special Needs, an increase in participants' understanding of the types of Children with Special Needs, and also an increase in participants' understanding of the treatment efforts that can be taken for children with special needs.